(untitled) (Journal of Applied Oral Science, 2021)
Objectives: This study assessed the incidence and variability features of root canals system (RCS) and their ramifications according to Pucci & Reig (PR) (1944) and the American Association of Endodontists (AAE) (2017) by micro-computed tomography (μCT). Methodology: 500 representative extracted human teeth of each tooth group (n=50) (maxillary/mandibular central and lateral incisors, canines, first and second premolars and molars) were scanned by μCT with a resolution of 26.70 μm. The reconstructed cross-sections images and the visualization of the continuous slices in the transversal axis were performed using DataViewer software. RCS were classified according to Pucci & Reig (main canal, collateral canal, lateral canal, secondary canal, accessory canal, intercanal, recurrent canal) and AAE (main canal, accessory canal, lateral canal). The apical deltas were assessed for both classifications. The prevalence of apical deltas was evaluated using the Chi-squared test (p<0.05). Results: According to PR, a higher incidence of lateral canals was observed in maxillary canines (10%), central incisors (8%) and first premolars (6%). Using AAE, the highest incidence of lateral canals was observed in the mandibular first premolars (85%), first and second molars (84%), lateral incisors (67%), canines (59%), and in maxillary first premolars (52%). Regarding accessory canals, the PR showed a frequency in 2% of the maxillary lateral incisors and maxillary and mandibular first premolars and 3% of mandibular first and second molars. On the other hand, the AAE showed the highest incidence of accessory canals in 86% of the maxillary first premolars, 71% in mandibular lateral incisors, 69% in mandibular first premolars, 65% in mandibular canines, and 56% in maxillary canines. The PR showed the lowest incidence of apical deltas for all dental groups when compared with AAE (p=0.004). Interestingly, distal canals in maxillary molars showed a significant discrepancy between classifications (p=0.027). Conclusions: μCT enabled accurately describing the RC system and related ramifications, adding to the PR and AAE classifications, with some discrepancies reported for maxillary molars. Clinical Relevance This μCT study enabled a thorough description of the variability among root canals and their ramifications, including clinically relevant details on the presence and location of lateral canals and accessories in all human tooth groups, beyond the currently existing classification systems.